2000
DOI: 10.1046/j.1365-2958.2000.01808.x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation of CpsD negatively regulates capsular polysaccharide biosynthesis in Streptococcus pneumoniae

Abstract: SummaryIn Streptococcus pneumoniae, the first four genes of the capsule locus (cpsA to cpsD) are common to most serotypes. By analysis of various in-frame deletion and site-directed mutants, the function of their gene products in capsular polysaccharide (CPS) biosynthesis was investigated. We found that while CpsB, C and D are essential for encapsulation, CpsA is not. CpsC and CpsD have similarity to the aminoterminal and carboxy-terminal regions, respectively, of the autophosphorylating protein-tyrosine kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
260
1
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(286 citation statements)
references
References 49 publications
21
260
1
4
Order By: Relevance
“…Thus, when Wzc is phosphorylated, no colanic acid is synthesized by bacteria, whereas when Wzc is dephosphorylated by Wzb, colanic acid is produced. The same observation has been made in Streptococcus pneumoniae where autophosphorylation of the kinase CpsD decreases its activity and, consequently, lowers the production of capsular polysaccharides (12).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Thus, when Wzc is phosphorylated, no colanic acid is synthesized by bacteria, whereas when Wzc is dephosphorylated by Wzb, colanic acid is produced. The same observation has been made in Streptococcus pneumoniae where autophosphorylation of the kinase CpsD decreases its activity and, consequently, lowers the production of capsular polysaccharides (12).…”
supporting
confidence: 64%
“…Indeed, although intermolecular autophosphorylation of Wzc at the C-terminal tyrosine cluster (five tyrosines from position 708 to position 715) is stimulated by intramolecular autophosphorylation at Tyr 569 (24), autophosphorylation of the S. pneumoniae kinase CpsD only occurs on the tyrosine cluster when the membrane protein modulator CpsC is also present (Fig. 1) (11,12). Several studies have been performed to assess the biological role of phosphorylation of the tyrosine cluster located at the C-terminal end of PTKs.…”
mentioning
confidence: 99%
“…We have unpublished data showing that fusion of GFP to the C-terminus of Wzz SF results in an 85 % reduction in Wzz activity (Daniels, 1999) and furthermore, studies of hybrid Wzz proteins also support the idea that the C-terminus is important for function (Daniels & Morona, 1999). While post-translational regulation of Wzz activity has not been demonstrated as yet, activity of the related PCP2 proteins, Wzc and CpsC/D, is affected by phosphorylation that is mediated via cytoplasmic domains or subunits of these proteins (Morona et al, 2000a;Vincent et al, 1999;Wugeditsch et al, 2001). It may be possible that a similar mechanism for regulating the activity of Wzz pHS2 and other Wzz proteins exists.…”
Section: Discussionmentioning
confidence: 95%
“…BLASTP analysis showed that PhpA is a member of the PHP superfamily. PhpA shared 28, 24, 23, 28, (Morona et al, 2002) and EpsB from Streptococcus thermophilus (Minic et al, 2007), respectively (Fig. S1, available with the online version of this paper).…”
Section: Comparative Sequence Analysis Of Phpamentioning
confidence: 99%
“…PHPs are divalent metal ion-dependent enzymes, and the phosphatase activities of PHPs are stimulated by various metal ions (Morona et al, 2002;Hagelueken et al, 2009). The protein phosphatase activity of PhpA required Mn 2+ or Co 2+ as an essential cofactor (Table 1).…”
Section: Enzymic Characterization Of Phpamentioning
confidence: 99%